Characteristics of the Million Women Study Participants Who Have and Have Not Worked at Night - Wang, Xiao-Si; Travis, Ruth C; Reeves, Gillian; Green, Jane; Allen, Naomi E; Key, Tim J; Roddam, Andrew W; Beral, Valerie (Scandinavian Journal of Work, Environment ＆ Health, 2012)
Objectives The aim of this study was to compare the characteristics of women who had and had not worked at night in terms of their risk factors for common disease, indicators of general health, social activities, employment, and sleep behavior. Methods The Million Women Study is a large prospective cohort study of women's health in the United Kingdom with 1.3 million women recruited during 1996—2001 (aged 50—64 years) through 66 National Health Service breast screening centers. We analyzed the data from a random sample of 41 652 participants who, in 2009—2010, reported their history of night work. Results Of the participants, 1 in 8 women (13%) reported that they had ever worked at night and 1 in 50 (2%) reported working at night for ≥20 years. For 33 sociodemographic, behavioral, reproductive, and hormonal factors examined, 20 showed highly significant differences between "ever" and "never" night workers (P<0.0001); 12 showed significant trends by duration of night work (P<0.01). In particular, compared to women who had never worked at night, women who had worked at night were more likely to (i) be of lower socioeconomic status [the odds ratio (OR) for ever versus never night workers of being in the lowest third of socioeconomic status was 1.15, 99% confidence interval (95% CI) 1.06—1.25]; (ii) have ever used hormone replacement therapy (HRT) for the menopause (OR 1.43, 99% CI 1.33—1.55); (iii) be current smokers (OR 1.37, 99% CI 1.19—1.58); and (iv) be obese (OR 1.26, 99% CI 1.15—1.37). Compared to women who had never worked at night, women who had worked at night for ≥20 years were more likely to be (i) of lower socioeconomic status (OR 1.28, 99% CI 1.04—1.57); (ii) nulliparous (OR 1.47, 99% CI 1.12—1.91); (iii) current smokers (OR 1.63, 99% CI 1.18—2.25); and (iv) obese (OR 1.55, 99% CI 1.25—1.93). Former night workers were more likely than never night workers to report a range of sleep disturbances, including poor quality of sleep (OR 1.15, 99% CI 1.01—1.31) and having to take medication to sleep (OR 1.35, 99% CI 1.15—1.60). Conclusions Women who reported having worked at night were substantially different from those who reporting never having worked at night and many of the differences would put "ever night workers" at increased risks of cancer, vascular disease, and many other common conditions.